Writing and research : a guide for theological students - SMITH, Kevin, Gary (Carlisle Langham Global Library, 2016)
This publication provides helpful guidelines and illustrations on all the elements that go into producing an academic work. Combining specific instruction on researching and preparing an academic work, as well as practical advice for task management, makes this an ideal go-to guide for students and supervisors alike.
Includes common Biblical abbreviations, index